Evaluation of the validity of the physical exercise peer support questionnaire for college students - Lin Luo; Lin Luo; Lin Luo; Xiuxiong Yang; Xiaojin Zeng; Naiqing Song; Naiqing Song; Ling Zhou; Liping Zhang; Yongbin Yang; Jie Yang (Frontiers Media S.A., 2022)
Peer support for physical exercise is defined as behaviors such as mutual or one-way provision of material help and/or emotional care and companionship between peers in the physical environment and/or physical behavior. The assessment of peer support is complex and based on reasoning. Trustworthy assessment processes need to provide sufficient evidence of validity. The purpose of this study was to organize, collect, and use Kane's validity framework to provide validity evidence for the identification of peer support for physical exercise among college students. The article describes the experience of using the framework in this study, considers data related to the four inferences (scoring, generalization, extrapolation, and implication) that emerge from the assessment process. The findings of the study are then interpreted through the four inferences to determine whether this evidence supports the purpose of this study. Based on Kane's framework to explain the validity process of this study, the study concludes that the evidence in terms of scoring, generalization, extrapolation, and implication supports the use of the PEPSQ for the identification of physical exercise peer support among college students.